Mundane mobilities in mundane places? The role of proximity tourism in place attachment in the rural north - Nousiainen, Minna (fi=Lapin yliopisto|en=University of Lapland|, 2022)
Contemporary times are defined by layers of interconnected local and global mobilities and constant flow of people, ideas, things and commodities. Consequently, life consists of different kind of mobile practises that are blurring the boundaries between the ordinary everyday life and more exotic “other”. In doing so, mobilities change the ways in which we create relationships with different places. Thus, the mobility turn has also direct impacts to tourism and distinct tourist spaces and calls for alternative ways of negotiating tourism mobilities and practices. Proximity tourism has become an increasing trend in tourism. As a low-carbon mode of travel it has been seen as an alternative for international mass tourism, on the one hand, and a way to tackle some of the economic challenges of the industry, such as seasonality, on the other. At the same time, it presents a new understanding of tourism mobilities as an interplay with the landscape that is simultaneously ordinary and extraordinary. However, studies on the meanings of proximity tourism in local communities are still relatively scarce. This thesis aims to explore how proximity tourism contributes to place attachment of local people in the rural north. In doing so, it also seeks to increase the understanding of proximity tourism as a phenomenon and the meanings allocated to proximity tourism experiences. The theoretical framework of the study is based on the perceptions of place in the new mobilities paradigm (Sheller & Urry, 2006). The study was conducted by interviewing local people in Pello, Finnish Lapland. The data consists of six interviews with nine interviewees of different ages and resident times in Pello. The data was analysed using qualitative content analysis. The findings of the study demonstrate that proximity tourism contributes significantly to the place attachment of the interviewees by offering meaningful experiences and interactions with the landscape. The participants make sense of their proximity tourism experiences through ...